FOOD SAFETY PRACTICES AND ASSOCIATED FACTORS AMONG MOTHERS OF UNDER-FIVE CHILDREN IN TIRUPATI: A COMMUNITY-BASED CROSS-SECTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: In India, most of the deaths among children (